Design of a modular snake robot - Wright, C.; Johnson, A.; Peck, A.; McCord, Z.; Naaktgeboren, A.; Gianfortoni, P.; Gonzalez-Rivero, M.; Hatton, R.; Choset, H. (2007 IEEE/RSJ International Conference on Intelligent Robots and Systems, 2007)
Many factors such as size, power, and weight constrain the design of modular snake robots. Meeting these constraints requires implementing a complex mechanical and electrical architecture. Here we present our solution, which involves the construction of sixteen aluminum modules and creation of the Super Servo, a modified hobby servo. To create the Super Servo, we have replaced the electronics in a hobby servo, adding such components as sensors to monitor current and temperature, a communications bus, and a programmable microcontroller. Any robust solution must also protect components from hazardous environments such as sand and brush. To resolve this problem we insert the robots into skins that cover their surface. Functions such as climbing the inside and outside of a pipe add a new dimension of interaction. Thus we attach a compliant, high-friction material to every module, which assists in tasks that require gripping. This combination of the mechanical and electrical architectures results in a robust and versatile robot.